A potential of banana flower and pseudo‐stem as novel ingredients rich in phenolic compounds. (19th May 2021) - Ramírez‐Bolaños, Sara; Pérez‐Jiménez, Jara; Díaz, Sara; Robaina, Lidia
Abstract : A preliminary approximation to characterizes the banana culture by‐products, like banana flowers and banana pseudo‐stem, including a comprehensive analysis of the phenolic compounds by HPLC‐MS was performed in this study. The results suggest that both materials showed to have a potential for their use as novel food ingredients.